Narmada and Dristi Recently released urdbean varieties for spring cultivation - Gupta, Debjyoti Sen; Dixit, G P (Indian Farming, 2024)
This article describes two varieties of urdbean (Narmada and Dristi) released and notified in 2023 for general cultivation during spring season in Madhya Pradesh.